In-vitro Antibacterial Evaluation of Some Fluoroquinolone Derivatives Against Food Borne Bacteria - N. Shariatifar; M. Rezaei; M. Sayadi; M. H. Moshafi; M. Saeedi; N. Mohammadhosseini; S. Moghimi; A. Foroumadi (Journal of Sciences, Islamic Republic of Iran)
Food poisoning has been emerged as a worldwide health issue and related illness in both developed and developing countries confirms its significance as an important public health priority.In vitro antibacterialevaluationof nine fluoroquinolone derivatives against food borne bacteria including Gram-positive (Staphylococcus aureus) and Gram-negative (Salmonella enterica, Escherichia coli, Yersinia enterocolitica, Vibrio cholerae) organisms was developed using agar dilution technique and compared with ciprofloxacin and norfloxacin as reference drugs.Most compounds showed good activity against Gram-positive and the Gram-negative bacteria. All compounds were active against Staphylococcus aureus (MIC=3.12-6.12µg/mL) and compounds 1a, 1c-e, 2a, and 3c(MIC=3.12µg/mL) exhibited excellent antibacterial activity in comparison to ciprofloxacin and norfloxacin (MIC=6.25µg/mL). Fluoroquinolone derivatives exhibited good activity against food borne bacteria and are appropriate candidates for food poisoning prevention.